2013
DOI: 10.1002/glia.22605
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐specific activation of TNFR2 promotes oligodendrocyte maturation by secretion of leukemia inhibitory factor

Abstract: Tumor necrosis factor (TNF) and its receptors TNFR1 and TNFR2 have pleiotropic effects in neurodegenerative disorders. For example, while TNFR1 mediates neurodegenerative effects in multiple sclerosis, TNFR2 is protective and contributes to remyelination. The exact mode of TNFR2 action, however, is poorly understood. Here, we show that TNFR2-mediated activation of the PI3K-PKB/Akt pathway in primary astrocytes increased the expression of neuroprotective genes, including that encoding the neurotrophic cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 49 publications
2
89
0
Order By: Relevance
“…Accordingly, TNFR1 antagonists such as ATROSAB should be superior to conventional anti-TNF drugs in the treatment of neurodegenerative diseases, as they spare TNFR2 and even enhance TNFR2 signaling but still block detrimental signals transmitted via TNFR1. In addition to the potential therapeutic use of TNFR1-specific antagonistic antibodies, TNFR2-selective agonists seem to be particularly suitable to treat inflammatory, demyelinating diseases, because next to the direct neuroprotective effects shown in this report, data from different laboratories outline that TNFR2 is also involved in immune suppression via expansion and stabilization of regulatory T cells (41)(42)(43)(44)(45)(46)(47), and induces remyelination (9,13,14). Thus, like TNFR1 antagonists, TNFR2 agonists might promote therapeutic effects via multiple cellular targets.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Accordingly, TNFR1 antagonists such as ATROSAB should be superior to conventional anti-TNF drugs in the treatment of neurodegenerative diseases, as they spare TNFR2 and even enhance TNFR2 signaling but still block detrimental signals transmitted via TNFR1. In addition to the potential therapeutic use of TNFR1-specific antagonistic antibodies, TNFR2-selective agonists seem to be particularly suitable to treat inflammatory, demyelinating diseases, because next to the direct neuroprotective effects shown in this report, data from different laboratories outline that TNFR2 is also involved in immune suppression via expansion and stabilization of regulatory T cells (41)(42)(43)(44)(45)(46)(47), and induces remyelination (9,13,14). Thus, like TNFR1 antagonists, TNFR2 agonists might promote therapeutic effects via multiple cellular targets.…”
Section: Resultsmentioning
confidence: 82%
“…Because most of the proinflammatory actions of TNF are mediated by TNFR1, a more effective therapeutic approach could be the selective blocking of TNFR1 signaling; this would spare TNFR2 signaling, which has been implicated in various protective and regenerative responses, particularly in the central nervous system: TNFR2 signaling was shown to promote neuronal survival and oligodendrocyte regeneration in in vivo models of ischemic and neurotoxic insults (9,10), respectively. Specific activation of TNFR2 rescues neurons (11) and oligodendrocytes (12) from oxidative stress and promotes oligodendrocyte differentiation and myelination (13,14). In addition, TNFR2 signaling protects neurons from glutamate-induced excitotoxicity in vitro (15,16).…”
mentioning
confidence: 99%
“…In addition to paracrine effects on motor neurons, astrocytes also express both TNFα receptors (TNFR1 and TNFR2) and TNFα can act on astrocytes to cause a diverse set of changes (Fischer, Wajant, Kontermann, Pfizenmaier, & Maier, 2014; Tezel, Li, Patil, & Wax, 2001) Thus, TNFα released from mutFUS astrocytes may contribute to astrocytic changes through autocrine mechanisms. Two recent studies have demonstrated that TNFα contributes to the induction of neurotoxic astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…DAMP signaling then leads to the activation of caspase 1, which in turn cleaves pro-IL-1 into active IL-1β (Walsh et al, 2014a). Upon activation by IL-1β, astrocytes can release large amounts of innate immune inflammatory mediators including several complement cascade proteins; cytokines including tumor necrosis factor (TNF), IL-1β, IL-6; and chemokines with CC (cysteine-cysteine) and CXC (cysteine-other amino acids-cysteine) motifs including CCL2, CXCL1, CXCL10, and CXCL12 (Bezzi et al, 2001;Fischer et al, 2014;Johnstone et al, 1999;Marz et al, 1999;Olmos and Llado, 2014;Santello and Volterra, 2012;Takahashi et al, 2003a;Torres-Platas et al, 2014b;Xie et al, 2003). This state is also associated with impaired glutamate clearance and oxidative stress, both of which contribute to excitotoxicity Tilleux and Hermans, 2007;Zou and Crews, 2005).…”
Section: Immune Regulationmentioning
confidence: 99%